Linear Algebra: A Modern Introduction

Published by Cengage Learning
ISBN 10: 1285463242
ISBN 13: 978-1-28546-324-7

Chapter 2 - Systems of Linear Equations - 2.1 Introduction to Systems of Linear Equations - Exercises 2.1 - Page 63: 26



Work Step by Step

Consider $x_1=-1$. and $-\dfrac{1}{2}x_1+x_2=5 \implies -\dfrac{1}{2}(-1)+x_2=5$ or, $x_2=\dfrac{9}{2}$ Now, $\dfrac{3}{2}x_1+2x_2+x_3=7 \implies \dfrac{3}{2}(-1)+2(\dfrac{9}{2})+x_3=7$ or, $x_3=\dfrac{-1}{2}$ Our result is : $(x_1,x_2,x_3)=(-1,\dfrac{9}{2},\dfrac{-1}{2})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.